PENERAPAN MODEL PEMBELAJARAN INVESTIGASI KELOMPOK BERBASIS GAYA BELAJAR UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR BAHASA INGGRIS SISWA KELAS VIII SMP NEGERI 1 PULAU PINANG - Emy Yuliany; Bambang Sahono (UNIB Press, 2020)
The main purpose of this research is to describe and interpret the application and effectiveness of group investigation learning method based on learning styles to improve collaboration and learning achievement of English students in eighth grade of SMP Negeri 1 Pulau Pinang. The method used in this research is mixed method. The type of mixed research method used is sequential exploratory. This type is most appropriate in classroom action research because in testing hypotheses with quasi-group experiment not conducted randomly, but paired, but there is one controlled variable that is the initial ability of students to be the same (tested the average pretest of the experimental and control classes with the test –T). In this research, the first step will be filled with qualitative data collection and analysis, then collecting and analyzing quantitative data. The techniques used in Classroom Action Research to collect data include observation, tests, and questionnaires. Based on the results of data analysis, the category of cooperation for cycle I was lacking, cycles II and III were good. The average post test score per cycle has increased. The results of the t-test formula calculation for quasi-experiments show that there are significant differences between the grades of students in the experimental class and in the control class. The results of this study indicate that the learning method of group investigation based on learning styles is effective in increasing cooperation and learning achievement of English students in eighth grade of SMP Negeri 1 Pinang in 2019 - 2020 school year.